2018
DOI: 10.17323/1813-8691-2018-22-2-197-227
|View full text |Cite
|
Sign up to set email alerts
|

The Pathways That Lead Youth in NEET: The Case of Russia

Abstract: Зудина Анна Алексеевна -к.соц.н., научный сотрудник Центра трудовых исследований Национального исследовательского университета «Высшая школа экономики».

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
6
0
3
Order By: Relevance
“…Experience confirmed that employees participating in outplacement can find a new job faster [81,82]. From this point of view, the most vulnerable group is just young employees [90], which can be a serious social problem, especially for young people who have never been employed [91].…”
Section: Discussionmentioning
confidence: 99%
“…Experience confirmed that employees participating in outplacement can find a new job faster [81,82]. From this point of view, the most vulnerable group is just young employees [90], which can be a serious social problem, especially for young people who have never been employed [91].…”
Section: Discussionmentioning
confidence: 99%
“…This occurs both in the case of those who find employment, because it is a job of poor quality, and in the case that they do not find it, because they could fall into discouragement. In this sense, the academic literature points out that the incidence of the number of NEETs is related to the socio-economic environment [5,7] and also with the situation of social vulnerability [16][17][18], mainly represented through the risk of poverty and social exclusion. Hence, the importance of analyzing the vulnerability of young people in their access to the labor market, considering the socio-economic environment in which they have developed, is identified.…”
Section: The Economic Environment Vulnerability and Young Peoplementioning
confidence: 99%
“…Additionally, it is worth highlighting that this problem goes beyond a specific group to become a social problem that has an important projection in the future [2], since the probability of finding a permanent job for those young people who previously were in the NEET position is lower and they assume a higher risk of precarious employment and other social issues, which even could come to a lack of trust in social institutions [18]. In all the countries of the European Union, the NEETs register high unemployment rates, and many of them, when finishing the basic or compulsory education, do not continue studying either.…”
Section: The Economic Environment Vulnerability and Young Peoplementioning
confidence: 99%
See 2 more Smart Citations